QUALITY EVALUATION AND SURVEY OF THE ESSENTIAL NEED FOR DRUG INFORMATION CENTERS - Wen, Ming Ming; Aref, Heba; Abozaid, Ahmad; Kandil, Nahla Hesham; Elsobky, Yasmin Hussein (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: The first objective of this work was to examine the services provided by six drug information centers (DICs) in Alexandria, Egypt. The second objective was to evaluate the quality of the replies to the drug information query. The third objective was to assess the conceptual need of DICs from community pharmacists, other health care professionals and the general public. Methods: This study was conducted through three stages. Stage I was a field survey to assess predefined parameters in the current DICs in Alexandria. Stage II was a retrospective cross-sectional study to assess the quality of the drug information replies through an external expert review process. Stage III was a population survey and thematic analysis using questionnaires and interview recording. Results: Activities of DICs include: DIR answering service (100%), adverse drug reaction reporting (100%), issuing bulletins (83.3%), education (83.3%), drug use evaluation (50%) and participation in P and T committees (33.3%). The most frequent question categories asked were dosing, side effects, treatment guidelines and drug interactions. Half of the DICs were affiliated with hospitals; however, a general lacking confidence level of these DICs on the professionalism and the impact on patient care for the DIC services provided was identified. There was an obvious problem in formatting the ultimate question in a question format rather than a sentence format in all DICs. The most accurately answered request was adverse drug reactions. All surveyed groups considered that it is very important to have a DIC accessible to the community free of charge. Conclusion: It is necessary to establish an university-based DIC to incorporate training, education and research into the existing services. A DIC network with definitive standards of services in the future should provide safe and effective quality-assured pharmaceutical care to meet the needs and expectations of the community and improve its delivery to the public. The results and recommendations of this study can be inspired and generalized to other developing countries that have similar health systems as in Egypt. Â 